Chinese Americans and the politics of race and culture - Hsu, Madeline Yuan-yin (Asian American history and culture., 2008)
The essays in this book, written by people involved either involved in the strike (graduate students, faculty, organizers) or who are nationally recognized writers on academic labor, offers lessons on what the GSOC strike says about the current role of the university in public life, and how the pressure for universities to realign themselves along the lines of private corporations has broad implications for the future of higher education.